Implementasi Undang-Undang Nomor 22 Tahun 2009 pada Pengawasan Jembatan Timbang Sungai Lansek Perspektif Siyasah Tanfiziyah - Nila Maharani; Ali Rahman (AHKAM, 2026)
Although weighbridge supervision is an important instrument for enforcing Law Number 22 of 2009 to ensure traffic safety and protect road infrastructure, its implementation at the Sungai Lansek Motor Vehicle Weighing Implementation Unit (UPPKB) continues to face various constraints, resulting in suboptimal supervisory effectiveness. This study aimed to analyze the implementation of Law Number 22 of 2009 in the supervision of the Sungai Lansek Weighbridge and examine it from the perspective of Siyasah Tanfiziyah. The study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving UPPKB officers, truck drivers, and community members. The data were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that supervision had been conducted through document inspection, examination of the physical condition and dimensions of vehicles, vehicle weighing, and enforcement in accordance with standard operating procedures. However, the effectiveness of supervision remained constrained by limited human resources, budgets, and supporting facilities, suboptimal interagency coordination, and low driver compliance, as drivers avoided weighing because they carried excessive loads and considered economic factors. From the perspective of Siyasah Tanfiziyah, the implementation of supervision had essentially reflected the principles of justice, trustworthiness, and public welfare, although its implementation was not yet fully optimal. This study contributes to the development of Siyasah Tanfiziyah studies in transportation policy implementation and provides practical implications regarding the need to strengthen resources, improve interagency coordination, and optimize the supervision system to enhance driver compliance, traffic safety, and the protection of road infrastructure.